Hospital remote monitoring embedded system and nursing intervention for patients with anxiety and insomnia - Chang, Xiaoman; Hao, Lei; Sun, Chong; Chen, Shengxia; Wang, Yan; Wang, Yurong; Tang, Xiaosun (Microprocessors and microsystems, 2021)
Most of the systems used in medicine are based on embedded electronic systems. These medical systems are mainly made up of embedded electronic components installed primarily in today's medical methods. The increasing use of these systems is also oriented towards adequate supervision and useful home care applications from an economic perspective. Future trends in monitoring applications for remote monitoring of embedded systems require architectural and infrastructure complexity to reduce costs and benefits. There is an outflow of modern technology for sensing and transmitting microchip data processing technology to promote better health guidance with first aid. The purpose of this study is to evaluate the feasibility and therapeutic efficacy estimates based on the results of the Augmented Data Analysis Technique (ADAT). Medication intercessions for the anticipation and treatment of insanity have restricted advantages, and significant expenses are related to results' danger. Clinical rules suggest the improvement of non-pharmacological intercessions to forestall incoherence, however powerful preventive procedures remain unestablished. It is to analyze the data of the proposed Augmented Data Analysis Technique (ADAT), give accurate results with the help of Xilinx FPGA software, and be the subject of the Internet of Things to monitor the health of patients.